Comparison of fluorescence optical imaging, ultrasonography and clinical examination with magnetic resonance imaging as a reference in active rheumatoid arthritis patients. Issue 2 (3rd April 2018) - Hirano, Fumio; Yokoyama-Kokuryo, Waka; Yamazaki, Hayato; Tsutsumino, Michi; Sakai, Ryoko; Satoh, Shiro; Kimura, Tomo; Tojo, Naoko; Kohsaka, Hitoshi; Harigai, Masayoshi
Abstract: Background: Fluorescence optical imaging with indocyanine-green enhancement (FOI) is a new imaging modality for the assessment of hand arthritis. The objective of this study was to compare performance profiles of clinical examination (CE), US and FOI using MRI as a reference in the same active rheumatoid arthritis (RA) patients. Methods: CE, US, FOI and MRI were performed on six subjects with active RA. Each sequence of FOI was divided into three phases based on indocyanine-green dynamics and the joints were graded semi-quantitatively. Sensitivities and specificities of CE, US and FOI were calculated using the RAMRIS synovitis score >0 as a reference in a total of 30 joints (the second to fifth metacarpophalangeal (MCP) joints and the wrist of the clinically dominant hand). Results: FOI showed sensitivities and specificities, respectively, of 85% and of 94% for Phase-1 and 69% and 94% for Phase-2. Sensitivities and specificities were 100% and 35% for CE (tender or swollen), 92% and 41% for gray scale US, and 77% and 100% for color-Doppler US. Conclusions: The performance characteristics of FOI in detection of synovitis in patients with active RA are comparable to those of US and more specific than CE. FOI has a potential as an assessment modality of RA.